2012
DOI: 10.4103/0250-474x.107076
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric estimation of azithromycin in tablets

Abstract: The present manuscript describes a simple, sensitive, accurate, precise and economical visible spectrophotometric method for the estimation of azithromycin from tablet formulation. The method is based on the reduction of potassium permanganate in alkaline medium with azithromycin. The measurement of decrease in absorbance of potassium permanganate at 547 nm was done, as it decolourises upon reduction by azithromycin. The method was used to determine between 2 and 20 μg/ml of azithromycin in the final measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…A spectrophotometric method was used for Azin determination based on the reduction of potassium permanganate in an alkaline medium with Azin and the solution was measured at 547 nm [19].…”
Section: Synthesis Of Membrane and Electrode Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…A spectrophotometric method was used for Azin determination based on the reduction of potassium permanganate in an alkaline medium with Azin and the solution was measured at 547 nm [19].…”
Section: Synthesis Of Membrane and Electrode Constructionmentioning
confidence: 99%
“…Jayanna et al [19] described a simple, sensitive, accurate, precise and economical visible spectrophotometric method for estimation of Azin in tablet formulation.…”
Section: Introductionmentioning
confidence: 99%
“…As these drugs are frequently co-administered in various infections, an effective, simple and specific analytical method is required for simultaneous estimation, thereby it will be helpful in the quantification of drugs in the formulation as well as in the biological matrices. An extensive literature survey suggests that development of various analytical techniques such as ultraviolet (UV)-visible spectroscopy [1][2][3][4][5][6], HPLC [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], HPTLC [25][26][27][28] and LCMS [29][30][31][32] for quantification of these drugs either in individual or combination with other drugs. Recently, Krishna et al, [21] reported an RP-HPLC method with the help of sodium dihydrogen ortho-phosphate (pH-5.2): acetonitrile in the ratio of 70:30 (%v/v) as mobile phase.…”
Section: Introductionmentioning
confidence: 99%
“…The color is stable for 5 h for the concentration of drug in the range of 5-20 μg/ml and 1 h in the range of 25-40 μg/ml. It was reported in the previous work[13] that absorbance was measured after 30 min of preparation of standard drug solution using potassium permanganate. In the present method absorbance was measured after the preparation of standard drug solution.…”
mentioning
confidence: 99%